Fruit Stalk Extract from Chili Peppers (Capsicum annum L.) as a Natural Antioxidant to Inhibit Oxidation in Crude Palm Oil - Rahmiwati Hilma; Eka Tri Setya Wulandari; Zaldi Arman (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Fruit stalk of chili pepper (Capsicum annum L.) so far is still an untapped waste. The content of active compounds in fruit and fruit stalk of chili pepper (C. annum L.) is known to have good antioxidant activity. The purpose of this study was to evaluate the extract of fruit stalk of chili pepper in inhibiting the oxidation of crude palm oil (CPO). In this study, the extraction of fruit stalk of chili pepper (C. annum L.) was carried out with n-hexane (from now on referred to as CHE) solvent and with ethanol solvent (from now on referred to as CEE). CHE and CEE were analyzed for total phenolic and flavonoid analyzes. Next, an evaluation of antioxidant activity was carried out using the DPPH method. The effectiveness test of adding the two extracts to the quality of CPO was carried out for ten days using a Completely Randomized Design (CRD) analysis. The parameters observed were peroxide numbers, free fatty acids, and iodine numbers. Data were analyzed by ANOVA and followed by a Least Significance Different (LSD) test. The results show that the total phenolic value is 0.257 mg QE/g dry weight in CEE and 0.003 mg QE/g dry weight in CHE. Total flavonoid values are 0.155 mg QE/g dry weight in CEE and 0.003 mg QE/g in CHE. IC50 values for DPPH test extract are 223.72 μg/mL in CEE and 953.77 μg/mL in CHE. The test results of the effectiveness of the two extracts against CPO show thin CEE, and CHE significantly (P <0.05) influences to CPO free fatty acids, peroxide number, and iodine number. Both extracts can protect CPO from oxidation. CEE is more effective in maintaining CPO quality for ten days with free fatty acid values (2.1%), peroxide value values 0.48 meq/kg, and iodine number 54.8. Furthermore, this result meets the CPO quality standard, according to SNI-01-2901-2006.